(untitled) - UNESCO (Tokyo, 1968)
Proceeding of the international round table on the relations between Japanese and western arts. Addresses at the opening ceremony, speeches in commemoration of the Meiji centenary.
Keywords: Art, Japanese,Relations between Japanese and western arts